Strategi Pemasaran Dan Literasi Syariah Dalam Mendukung Pemberdayaan UMKM Masyarakat - Fitriani, Ajeng Pipit; Aldzu Pazeroma; Dwi Rahayu (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Broto Village is one of the villages in Slahung sub-district, Ponorogo district that has many village assets that have the potential to be developed, especially small snack food processing industries such as processed bananas, corn and family medicine (TOGA). The products of small industries that can be marketed today are sale of bananas, banana chips, corn marning, and various processed herbal medicine TOGA. However, it is very unfortunate that the sales of various processed snacks have not been maximized, due to the lack of marketing strategies both in terms of packaging and in terms of promotion. This is due to the lack of ability of Small and Medium Enterprize (UMKM) actors in terms of branding, packaging, and promotions both offline and online. Departing from the assets of the Small and Medium Enterprize (UMKM) actors who already have this small business, this management seminar and marketing strategy is feasible to carry out. In the implementation of the seminar, the enthusiasm of Small and Medium Enterprize (UMKM) actors was extraordinary. They participated in seminar activities from beginning to end. After the seminar, Small and Medium Enterprize (UMKM) actors also tried to apply the knowledge they had gained, by improving branding, packaging, starting to promote their products through social media and recording sales in the cash book. The results of the evaluation show the ability of Small and Medium Enterprize (UMKM) actors to increase. And, of course, a comprehensive evaluation and ongoing assistance will be needed in the future.